2020
DOI: 10.2139/ssrn.3516893
|View full text |Cite
|
Sign up to set email alerts
|

COMMD4 Functions with the Histone H2A-H2B Dimer for the Timely Repair of DNA Double Strand Breaks

Abstract: Genomic stability is critical for normal cellular function and its deregulation is a universal hallmark of cancer. Here we outline a previously undescribed role of COMMD4 in maintaining genomic stability, by regulation of chromatin remodelling at sites of DNA double-strand breaks. At break-sites, COMMD4 binds to and protects histone H2B from monoubiquitination by RNF20/RNF40. DNA damage-induced phosphorylation of the H2A-H2B heterodimer disrupts the dimer allowing COMMD4 to preferentially bind H2A. Displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…A single unrepaired DSB in a cell can be cytotoxic [22,47], additionally mutations or down-regulation of DNA repair proteins, associated with the repair of DSBs, are strongly linked with inherited cancer risk (BRCA1, BRCA2, ATM) [48][49][50][51]. Here, as we confirmed a role for COMMD1 in the repair of DSBs and as COMMD4 was previously shown to function in the repair of DSBs [35] and additionally a potential therapeutic target and prognostic factor in NSCLC [36], we investigated a similar role for COMMD1 in NSCLC. Initially, the expression of COMMD1 transcripts were evaluated using bioinformatic analysis of The Cancer Genome Atlas (TCGA) datasets (Figure 2A-E).…”
Section: Commd1 Gene Transcripts Are Upregulated In Nsclc and This Upsupporting
confidence: 83%
See 3 more Smart Citations
“…A single unrepaired DSB in a cell can be cytotoxic [22,47], additionally mutations or down-regulation of DNA repair proteins, associated with the repair of DSBs, are strongly linked with inherited cancer risk (BRCA1, BRCA2, ATM) [48][49][50][51]. Here, as we confirmed a role for COMMD1 in the repair of DSBs and as COMMD4 was previously shown to function in the repair of DSBs [35] and additionally a potential therapeutic target and prognostic factor in NSCLC [36], we investigated a similar role for COMMD1 in NSCLC. Initially, the expression of COMMD1 transcripts were evaluated using bioinformatic analysis of The Cancer Genome Atlas (TCGA) datasets (Figure 2A-E).…”
Section: Commd1 Gene Transcripts Are Upregulated In Nsclc and This Upsupporting
confidence: 83%
“…COMMD proteins containing a C-terminal COMM domain are novel potential anti-cancer therapeutic targets and prognostic markers [ 30 , 31 , 35 ]. The expression of COMMD4 [ 36 ] and COMMD9 were previously assessed in NSCLC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[54][55][56] We have recently demonstrated that COMMD4 functions by regulating the monoubiquitination of H2B, following the induction of DNA double-strand breaks. 57 We show that COMMD4 functions to limit the extent of epigenetic modification of the chromatin around the break site. Depletion of COMMD4 leads to a loss of RNF20/40 regulation and uncontrolled chromatin remodelling.…”
Section: Discussionmentioning
confidence: 81%